2004
DOI: 10.1017/s1466046604000237
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Behavior in a Tropical Environment: The Case of Small-Scale Gold Mining in Poconé, Brazil

Abstract: An estimated 50 tons of mercury (Hg) have been emitted by gold miners in the Bento Comes river basin, in the municipality of Poconb, Brazil, since the 1980s. Since the mid-l990s, the state agency for environmental protection, FEMA (FundaGZo Estadual do Meio Ambiente de Mato Grosso), has enforced regulations to reduce Hg emissions to air and water and has also implemented an environmental assessment program. The objectives of this study were to evaluate efforts to reduce emissions of Hg to air and water from ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Risks of contamination due to the use of the mercury from gold mining have been reported over two decades (Nogueira, Nascimento, Silva, & Junk, 1997;Tu¨mpling, Wilken, & Einax, 1995;Vieira, Alho, & Ferreira, 1995). In tropical wetlands, the rate of biomagnification of the mercury in the trophic web is high (Da Silva & Estanislau, 2015;Oliveira, Hylander, & e Silva, 2004;Vieira et al, 1995). Signs of this process have been already found in the Pantanal (e.g., Callil & Junk, 2009;Ceccatto et al, 2016;Del Lama, Rocha, Jardim, Tsai, & Frederick, 2011;Fonseca, Malm, & Waldemarin, 2005;Hylander et al, 2000;May Junior et al, 2017;Pietro-Souza et al, 2017;Vieira et al, 2011).…”
Section: Miningmentioning
confidence: 99%
“…Risks of contamination due to the use of the mercury from gold mining have been reported over two decades (Nogueira, Nascimento, Silva, & Junk, 1997;Tu¨mpling, Wilken, & Einax, 1995;Vieira, Alho, & Ferreira, 1995). In tropical wetlands, the rate of biomagnification of the mercury in the trophic web is high (Da Silva & Estanislau, 2015;Oliveira, Hylander, & e Silva, 2004;Vieira et al, 1995). Signs of this process have been already found in the Pantanal (e.g., Callil & Junk, 2009;Ceccatto et al, 2016;Del Lama, Rocha, Jardim, Tsai, & Frederick, 2011;Fonseca, Malm, & Waldemarin, 2005;Hylander et al, 2000;May Junior et al, 2017;Pietro-Souza et al, 2017;Vieira et al, 2011).…”
Section: Miningmentioning
confidence: 99%
“…A recent study of nine Amalgamation Centers in Brazil, all using retorts, revealed that the retorts managed to keep the ambient Hg levels below the occupational safety limit at only one center [44]. This should be mentioned when retorts are promoted, in order to avoid giving the mining community the false impression that exposures would be easily and completely eliminated.…”
Section: Miners Are Largely Unaware Of the Health And Environmental Rmentioning
confidence: 99%
“…For decades, concerns about mercury contamination in the global food supply -especially fish -have led to a burgeoning body of literature on mercury's effects on human health and the environment (Oliveira et al, 2004;Passos and Mergler, 2008). The toxic risks of mercury pollution have been examined in depth both in terms of risks experienced by populations living near local emission sources as well as more dispersed transboundary pollution (Bose-O'Reilly et al, 2010;Taylor et al, 2005;Telmer and Veiga, 2008;Tomicic et al, 2011).…”
Section: The Global Mercury Convention and Its Implications For The Gmentioning
confidence: 99%